DIVERSIDADE E DISTRIBUIÇÃO DE PEIXES EM MICROBACIAS HIDROGRÁFICAS NO ALTO RIO PARANÁ, MATO GROSSO DO SUL - NEVES, Gabriela Ribeiro; CÓRDOVA JÚNIOR, Renner Fernando da Silva; PINHO, Henrique Ledo Lopes; MINILLO, Alessandro; SÚAREZ, Yzel Rondon (ANAIS DO ENIC, 2025)
.